Distribution of Cetaceans in the Canary Islands (Northeast Atlantic Ocean): Implications for the Natura 2000 Network and Future Conservation Measures - Herrera, Inma; Carrillo, Manuel; Cosme de Esteban, Marcial; Haroun, Ricardo (Frontiers in Marine Science, 2021)
The Canary Islands waters are considered a hotspot for marine biodiversity, especially in the case of cetacean species. This feature is being used by a well-established whale-watching sector in different islands. Unfortunately, some cetacean species face a number of threats, from natural causes such as predators, but in many cases as consequence of either direct or indirect human impacts. In this study, we pay attention to the distribution pattern of cetacean species and the conservation role of the Natura 2000 Network, a set of Special Areas of Conservation (SACs) under the framework of the European Habitat’s Directive. The main objective of the designated SACs is the conservation of its biological and ecological diversity, ensuring the long-term survival of species, in our case, the cetaceans in the waters around the Canary Islands. The analysis of the distributional areas of cetaceans in the canarian archipelago was based on a large database cetacean with compiled sighting from 2007 to 2018. The results obtained allow us to identify the major marine areas around de Canary Islands where the largest number of individuals can be found, considering their interactions with environmental and biological parameters. Furthermore, the distribution maps of the concerned cetacean species were compared with extant Natura 2000 Network of SACs, highlighting the need to extend these areas into the open sea for greater conservation of marine mammals, and, consequently, some suggestions were proposed to improve its role as key environmental tool for cetacean conservation in European Atlantic waters.